Dimensions and Factors of Learning Engagement on Learners’ Academic Performance (American Journal of Arts and Human Science, 2025)
Learners’ engagement is a measure that reflects the learner’s participation in the learning process while academic performance is the measurement of learner’s achievement in different subject areas. This research sought to ascertain the dimensions and factors of learning engagement on academic performance of respondents. Specifically, this answer to what extent of the learning engagement in terms of its dimensions as to behavioral, cognitive, and emotional; the level of the learning engagement concerning of family, school, teacher, and peer; the level of the learners’ academic performance; the significant relationship between the dimension of learning engagement and their academic performance; and the significant relationship between the factors of learning engagement and their academic performance. The results showed that the level of learning engagement as to behavioral, cognitive, and emotional dimensions was high. The factors of learning engagement in terms of family, school, teacher, and peer were positive. Further, the academic performance of the learners was very satisfactory. On the other hand, the test of relationship between the learning dimension of engagement and the learners’ academic performance was significant. In the same way, the test of relationship between the factors of learning engagement and their academic performance was also significant. It can be concluded that the behavioral, cognitive, and emotional aspects together with the factors of learning engagement such as, family, school, teacher and peer are important to academic performance. It is recommended teacher should build a strong and encouraging relationship with their learners to significantly enhance engagement. At the same time, teachers should use collaborative learning strategies for it allow learners to develop a good understanding and a friendly relationship among his/her classmates.